2022
DOI: 10.3390/e24070934
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Entropy in Construct Specification Equations (CSE) to Improve the Validity of Memory Tests: Extension to Word Lists

Abstract: Metrological methods for word learning list tests can be developed with an information theoretical approach extending earlier simple syntax studies. A classic Brillouin entropy expression is applied to the analysis of the Rey’s Auditory Verbal Learning Test RAVLT (immediate recall), where more ordered tasks—with less entropy—are easier to perform. The findings from three case studies are described, including 225 assessments of the NeuroMET2 cohort of persons spanning a cognitive spectrum from healthy older adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…For the total NMM only three items showed significant DIF with regards to sub-groups but for the individual test RAVLT as many as five of fifteen items showed DIF with regards to sub-groups. This issue has, however, been studied in detail in one of our previous papers 25 . We concluded that this may be due to dimensionality issues but refrained from separating groups of items into subtests (for RAVLT for primacy and recency items) in an attempt to improve the unidimensionality as the measurement uncertainties become too large with only a handful of dichotomous items.…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the total NMM only three items showed significant DIF with regards to sub-groups but for the individual test RAVLT as many as five of fifteen items showed DIF with regards to sub-groups. This issue has, however, been studied in detail in one of our previous papers 25 . We concluded that this may be due to dimensionality issues but refrained from separating groups of items into subtests (for RAVLT for primacy and recency items) in an attempt to improve the unidimensionality as the measurement uncertainties become too large with only a handful of dichotomous items.…”
Section: Limitationsmentioning
confidence: 99%
“…However, only one item showed a significant x 2 , and removing the items did not significantly affect the model fit. In separate papers we report further on the issue of the so-called serial position effect that occurs in the word learning list tests for the items in the beginning (primacy) and the end (recency) of the lists 25,36,37 .…”
Section: Psychometric Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is an empirical matter if the traceability extends to other frames of reference. Elsewhere, one study identified the role of a construct specification equation as a recipe for producing “certified reference materials” for calibration of both the task difficulty and a person's ability ( 139 ).…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…The concept of entropy has more than once been useful in connection with medical applications (see, for instance, [ 7 , 8 , 9 ]). In particular, nonadditive entropies have been extensively used in image and signal processing in order to improve speed and clarity.…”
Section: Medical Applicationsmentioning
confidence: 99%